Long-term survival in idiopathic pulmonary arterial hypertension associated with massive pulmonary artery dilation - Petrovic, Vanja (Pulsus Group Inc, 2011)
The present report describes two patients with long-term survival after being diagnosed with idiopathic pulmonary arterial hypertension more than 20 years earlier. Both patients were treated with calcium channel blockers for several years and are currently maintained on bosentan, an oral endothelin receptor antagonist. Severe dilation of the main pulmonary arteries is present in both patients and may be related to long-term survival with idiopathic pulmonary arterial hypertension.